ANALISIS KONTRIBUSI PERPUSTAKAAN INDONESIAN VISUAL ART ARCHIVE DALAM PENGEMBANGAN SENI RUPA - Fridinanti Yusufhin (Nusantara Journal of Information and Library Studies (N-JILS), 2022)
This study aims to determine the contribution of the Indonesian Visual Art Archive (IVAA) Library in developing fine arts. This study uses descriptive qualitative, while for data collection using the method of observation, interviews, and documentation. To analyze the results of the research, using data reduction techniques, data presentation, and verification (drawing conclusions. From the results of the study it is known that IVAA has contributed to the development of fine arts, namely as a place of recreation and a source of information, as a preserver of works of art, as a place of recreation). reference to fine art collections, as a place of education, and as a place for creative writing in the field of fine arts. The obstacles in carrying out this role are limited funds, human resources, and most collections in foreign languages.Keywords: library contribution, Indonesian Visual Art Archive, fine artsABSTRAKPenelitian ini bertujuan untuk mengetahui kontribusi Perpustakaan Indonesian Visual Art Archive (IVAA) dalam mengembangkan seni rupa. Penelitian ini menggunakan kualitatif deskriptif, sedangkan untuk pengumpulan data menggunakan metode observasi, wawancara, serta dokumentasi. Untuk menganalisis hasil dari penelitian, yaitu menggunakan teknik reduksi data, penyajian data, serta verfikasi (menarik kesimpulan. Dari hasil penelitian diketahui bahwa IVAA memiliki kontribusi dalam mengembangkan seni rupa, yaitu sebagai tempat rekreasi dan sumber informasi, sebagai pelestari karya seni rupa, sebagai tempat referensi koleksi seni rupa, sebagai ltempat edukasi, dan sebagai wadah kreatifitas kepenulisan dalam bidang seni rupa. Hambatan dalam pelaksanaan peran tersebut yaitu dana yang terbatas, Sumber daya manusia, serta kebanyakan koleksi berbahasa asing.